Association Between Social Determinants of Health and Postoperative Outcomes in Patients Undergoing Single-Level Lumbar Fusions: A Matched Analysis. Issue 9 (1st May 2021) - Khalid, Syed I.; Maasarani, Samantha; Nunna, Ravi S.; Shanker, Rachyl M.; Cherney, Alecia A.; Smith, Jennifer S.; Reme, Anne-Isabelle; Adogwa, Owoicho
Abstract : Study Design: Retrospective cohort. Objective: The aim of this study was to analyze association between social determinants of health (SDH) disparity on postoperative complication rates, and 30-day and 90-day all-cause readmission in patients undergoing single-level lumbar fusions. Summary of Background Data: Decreasing postoperative complication rates is of great interest to surgeons and healthcare systems. Postoperative complications are associated with poor convalescence, inferior patient reported outcomes measures, and increased health care resource utilization. Better understanding of the association between Social Determinants of Health (SDH) on postoperative outcomes maybe helpful to decrease postoperative complication rates. Methods: MARINER 2020, an all-payer claims database, was utilized to identify patients undergoing single-level lumbar fusions between 2010 and 2018. The primary outcomes were the rates of any postoperative complication, symptomatic pseudarthrosis, need for revision surgery, or 30-day and 90-day all-cause readmission. Results: The exact matched population analyzed in this study contained 16, 560 patients (8280 [50.0%] patients undergoing single-level lumbar fusion with an SDH disparity; 8280 [50.0%] patients undergoing single-level lumbar fusion without a disparity). Both patient groups were balanced at baseline. The rate of symptomatic pseudarthrosis (1.0% vs. 0.6%, P  < 0.05) or any postoperative complication (16.3% vs. 10.4%, P  < 0.05) in the matched analysis was higher in the disparity group. The presence of a disparity was associated with 70% increased odds of developing any complication (OR 1.7, 95% CI 1.53–1.84) or symptomatic pseudarthrosis (OR 1.7, 95% CI 1.17–2.37). Unadjusted and adjusted sensitivity analyses yielded similar results as the primary analysis. Conclusion: Social Determinants of Health affect outcomes in spine surgery patients and are associated with an increased risk of developing postoperative complications following lumbar spine fusion. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textSocial Determinants of Health (SDH) affect outcomes in spine surgery patients. SDH disparities in patients undergoing single-level lumbar spine fusion are associated with 70% increased odds of developing any complication (odds ratio [OR] 1.7, 95% confidence interval [CI] 1.53–1.84) or symptomatic pseudarthrosis (OR 1.7, 95% CI 1.17–2.37).